Governing Human Well-Being Domestic and International Determinants - Bellinger, Nisha (Springer International Publishing, 2018)
This book provides a comprehensive explanation of human well-being outcomes by analyzing the role of domestic and international political factors. The well-being outcomes under study are the building blocks of development, and play a crucial developmental role in the lives of citizens, states, and the global community. The project introduces cases from Brazil, Japan, China, and Iraq, and proposes to answer some of the pressing questions that scholars and policy-makers alike have pondered over for years. Why are there large disparities between countries in the quality of life people lead? What factors account for the general well-being of mankind? How do we improve human lives? .